Anisotropic deformation characteristics of soft marine clay involved the change of b-values and stress direction. Issue 7 (3rd October 2017) - Wang, Yuke; Zhang, Junjing; Ma, Lu; Wu, Di
ABSTRACT: In actual engineering, soft clay foundations are in drained or partial drained conditions, it would be useful to establish reasonable constitutive relationship and provide guidance for engineering projects. A hollow cylinder apparatus is used to investigate the anisotropic deformation behavior of natural soft marine clay influenced by intermediate principal stress coefficient b and principal stress direction α . Tests were conducted by maintaining a fixed principal stress direction α relative to the vertical direction, while keeping the intermediate principal stress coefficient b constant. It was found that the anisotropic deformation behavior of natural soft clay is merely influenced by major principal stress direction α, but significantly influenced by intermediate principal stress coefficient b .